P09.19 Results from a prevalence study of neisseria gonorrhoea and chlamydia trachomatis in a community-based, peer-led hiv testing service. (13th September 2015) - Ryan, K; Powell, S; Leitinger, D; Stoové, M
Abstract : Introduction: PRONTO!, Victoria's community based rapid point of care (RPOC) testing service, opened in August 2013. RPOC syphilis testing was introduced in June 2014. To assess the need and feasibility of comprehensive STI testing at PRONTO! a Neisseria gonorrhoea (NG) and Chlamydia trachomatis (CT) testing trial was conducted in November–December 2014. We describe site specific positivity of NG and CT infection and the characteristics of gay, bisexual and other men who have sex with men (GBM) testing positive. Methods: All GBM testing for HIV between November 7-December 23 2014 were offered NG and CT testing, with clients instructed in the self-collection of anal, genital and throat swabs. Client characteristics were collected using standard PRONTO! client surveys and matched to test results. All clients with an infection were notified by telephone and referred to a high caseload clinic for treatment. Results: Among 239 clients, 186 (78%) opted to receive NG and CT tests and 35 (18.8%) tested positive for at least one of NG or CT. Of the 22 (11.8%) positive NG results, there were nine anal (5.0%), two urethral (1.1%), and 15 throat (8.2%) infections. Of the 17 (9.1%) positive CT results, there were 12 anal (6.6%), eight urethral (4.3%), and three throat (1.6%) infections. Twelve men (6.4%) tested positive for more than one STI or at multiple sites. Demographic and risk characteristics were largely similar between men testing positive or negative for NG and/or CT with the exception that group sex in the previous six months was associated with both CT (OR = 4.65; 95% CI = 0.96–7.3) and NG (OR = 2.54; 95% CI = 1.02–6.33) positivity. Conclusion: STI testing using self-collected samples is a feasible model for screening in a community-based RPOC testing service. The high prevalence of infections and acceptability testing for bacterial STIs supports the introduction of comprehensive STI screening at PRONTO!. Disclosure of interest statement: All authors have no conflicts to declare. The Victorian Department of Health funds the PRONTO! service which is run by the Victorian AIDS Council. The authors would like to acknowledge the NHMRC who provide funding to Kathleen Ryan as a public health scholarship recipient and Mark Stoové through a Career Development Fellowship. The authors gratefully acknowledge the contribution to this work of Victorian Operational Infrastructure Support Program received by the Burnet Institute.